GONZÁLEZ CALVO, José Manuel (2011): Escollos de sintaxis española. Cáceres: Universidad de Extremadura; 210 pp. - Jasmina Markič (Verba Hispanica, 2011)
GONZÁLEZ CALVO, José Manuel (2011): Escollos de sintaxis española. Cáceres: Universidad de Extremadura; 210 pp.